Peran Patroli Satuan Sabhara Dalam Mencegah Tindak Pidana Curanmor Di Wilayah Hukum Polres Kuningan - Kahfi, Kevin Asshabul (Police Studies Review, 2020)
This research is motivated by the high number of criminal acts of curanmor in Kuningan Police. Related to this, the purpose of this study is to describe the picture of a motor vehicle theft, describe the role of the Kuningan Police Sabhara Patrol Unit in the prevention of curanmor and describe the factors that influence why the occurrence of the curanmor and the obstacles of the Sabhara Unit it self in preventing curanmor. The theories and concepts used are routine activity theory, management theory, management elements theory, role concepts, sabhara concepts, prevention concepts and patrol concepts. This research, the approach used is qualitative and the method used is analytical descriptive. Data collection techniques used were interviews, direct and documented observations, and study of documents. Furthermore, the data obtained were analyzed by data reduction, data display, and conclusions. The results showed that the crime of motor vehicle theft in the jurisdiction of the Kuningan police was included in a prominent crime. Prevention efforts made by the Kuningan Police Sabhara Unit by optimizing the implementation of the patrol role starting from the form of patrols, implementation, routes, targets, and vulnerable times. The conclusion of the occurrence of motor vehicle theft is urged by the economic needs of the perpetrators and their ignorance and the unconsciousness of the community towards its own environmental security. The implementation of patrols is also less than optimal due to obstacles such as lack of budget for fueling motor vehicles, and the lack of patrol members. The advice that can be given in this research is the need for better management of Kasat Sabhara himself in carrying out his duties, especially in prevention efforts.